Synthesis, Crystal Structures, and DNA Binding Properties of Zinc(II) Complexes with 3-Pyridine Aldoxime - Konstantis F. Konidaris; Rigini Papi; Eugenia Katsoulakou; Catherine P. Raptopoulou; Dimitrios A. Kyriakidis; Evy Manessi-Zoupa (Bioinorganic Chemistry and Applications)
The employment of 3-pyridine aldoxime, (3-py)CHNOH, in ZnII chemistry has afforded two novel compounds: [Zn(acac)2{(3-py)CHNOH}]⋅H2O (1⋅H2O) [where acac- is the pentane-2,4-dionato(-1) ion] and [Zn2(O2CMe)4{(3-py)CHNOH}2] (2). Complex 1⋅H2O crystallizes in the monoclinic space group P21/n. The ZnII ion is five-coordinated, surrounded by four oxygen atoms of two acac- moieties and by the pyridyl nitrogen atom of the (3-py)CHNOH ligand. Molecules of 1 interact with the water lattice molecules forming a 2D hydrogen-bonding network. Complex 2 crystallizes in the triclinic P-1 space group and displays a dinuclear paddle-wheel structure. Each ZnII exhibits a perfect square pyramidal geometry, with four carboxylate oxygen atoms at the basal plane and the pyridyl nitrogen of one monodentate (3-py)CHNOH ligand at the apex. DNA mobility shift assays were performed for the determination of the in vitro effect of both complexes on the integrity and the electrophoretic mobility of pDNA.